A critical investigation of the relationship between masculinity, social justice, religious education and the neo-liberal discourse - Farrell, Francis (Education & training (London), 2014)
Purpose – The purpose of this paper is to critically investigate a group of year 11 boys’ relationship to RE in response to debates about boys’ underachievement in RE. Design/methodology/approach – Qualitative data were collected through observations and semi-structured interviews. Data analysis draws upon pro-feminist and poststructuralist theories of the gendered subject. Findings – The data presented in this paper reveals how RE functioned as a political space for the exploration of social justice issues that formed part of the boys’ daily experiences, serving to increase awareness and understanding of diversity. Research limitations/implications – At a time of curriculum change where RE has been marginalised by exclusion from the DfE's English Baccalaureate this paper also seeks to contribute to debates about education for social justice through critical, pluralistic RE within a neo-liberal policy context. Practical implications – RE is shown to be a potent educational resource for challenging pupils’ negative social practices and producing more reflexive masculine subjects. Social implications – The contribution of RE to ensuring greater understanding and dialogue requires reassertion and protection within the curriculum. Originality/value – The data presented shows that where RE is taken up by masculine subjects it offers an alternative discourse with potential to create community cohesion and interfaith dialogue.